2011
DOI: 10.1128/aac.01749-10
|View full text |Cite
|
Sign up to set email alerts
|

Trends towards Lower Antimicrobial Susceptibility and Characterization of Acquired Resistance among Clinical Isolates of Brachyspira hyodysenteriae in Spain

Abstract: The antimicrobial susceptibility of clinical isolates of Brachyspira hyodysenteriae in Spain was monitored, and the underlying molecular mechanisms of resistance were investigated. MICs of tylosin, tiamulin, valnemulin, lincomycin, and tylvalosin were determined for 87 B. hyodysenteriae isolates recovered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 39 publications
(55 reference statements)
7
79
1
3
Order By: Relevance
“…For valnemulin, the results were similar to those previously reported (Karlsson et al 1999, 2002, Rohde et al 2004, Hidalgo et al 2009, 2011, Zmudzki et al 2012, Alvarez et al 2013, Mirajkar & Gebhart 2013. The MIC50 results for tiamulin were higher than those published elsewhere, but the MIC90 was similar to the results obtained by Rohde et al (2004), Hidalgo et al (2011) and by Alvarez et al (2013). The resistance related to tiamulin and to the other pleuromutilins is derived from point mutations in the V domain of the 23S rRNA gene and the ribosomal protein L3 (Hidalgo et al 2011).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…For valnemulin, the results were similar to those previously reported (Karlsson et al 1999, 2002, Rohde et al 2004, Hidalgo et al 2009, 2011, Zmudzki et al 2012, Alvarez et al 2013, Mirajkar & Gebhart 2013. The MIC50 results for tiamulin were higher than those published elsewhere, but the MIC90 was similar to the results obtained by Rohde et al (2004), Hidalgo et al (2011) and by Alvarez et al (2013). The resistance related to tiamulin and to the other pleuromutilins is derived from point mutations in the V domain of the 23S rRNA gene and the ribosomal protein L3 (Hidalgo et al 2011).…”
Section: Discussionsupporting
confidence: 68%
“…The MIC50 results for tiamulin were higher than those published elsewhere, but the MIC90 was similar to the results obtained by Rohde et al (2004), Hidalgo et al (2011) and by Alvarez et al (2013). The resistance related to tiamulin and to the other pleuromutilins is derived from point mutations in the V domain of the 23S rRNA gene and the ribosomal protein L3 (Hidalgo et al 2011).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…hyodysenteriae and/or B. pilosicoli strains from numerous countries, including Australia (13), Belgium (20), the Czech Republic (21), Germany (22), Italy (23), Japan (24), Netherlands (25), Poland (26), Spain (27), Sweden (15), and the United Kingdom (28), were reported to have low susceptibilities to one or more antimicrobial agents. Some studies have also identified resistant strains in several farms or regions as a result of clonal dissemination (23,28).…”
mentioning
confidence: 99%
“…(Table 3). Most published studies have focused on the association between single nucleotide polymorphisms (SNPs) in genes encoding ribosomal RNA and ribosomal proteins and increased MIC to drugs that act by inhibiting protein synthesis inhibitors, including macrolides, lincosamides, pleuromutilins, doxycycline, chloramphenicol, and florfenicol (Pringle et al 2004(Pringle et al , 2007Hidalgo et al 2011;Verlinden et al 2011;Hillen et al 2014). Narrow-spectrum ␤-lactamases, including 13 enzymes related to OXA-63, have also been identified in B. pilosicoli (Meziane-Cherif et al 2008;Mortimer-Jones et al 2008;La et al 2015).…”
Section: Objective Measures Of Resistancementioning
confidence: 99%